Local family fiqh in Malaysia: an analysis of `urfi methodological framework - Haneef, Sayed Sikandar Shah; Sitiris, Miszairi; Mohd Yunus, Saidatolakma (IIUM Press, International Islamic University Malaysia, 2020)
The ongoing advocacy for developing local fiqh, among others, emphasizes an indigenous approach to evolving fiqh by highlighting the flaws in the dominant approach to family law reform and renewal. One of their methodological tools is to examine the existing family fiqh from its `urfi based content as well to explore ways of resolving new emerging usages and customs, which differ from customs of people in other communities in the Muslim world. Critics, however, have some misgivings about this approach and see it as a kind of post-modernist thinking, the thrust of which is to raise skepticism about religious content of any intellectual argument or advocacy. To rebut such an argument, following content analysis method, this paper argues by concluding that an Islamic juridical approach to insist on legislative significance of local custom in evolving a local family fiqh is governed by a set of methodological frameworks and parameters which can safeguard it against any suspicion for secularization.